Perancangan dan Implementasi Game Edukasi Interaktif Berbasis Web sebagai Media Pembelajaran Taman Kanak-Kanak - Tan, Kezia Sherafim Evangelista; Toni Wijarnoko Adi Putra; Budi Hartono (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Early childhood education requires engaging and interactive learning media to enchance student’s motivation and participation. However, learning activities in many kindergartens are still dominated by conventional methods, which are less effective in attracting children’s attention. This study aims to design and implement a web-based interactive educational game as an alternative learning medium for early childhood education. This research applies the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through observation, questionnaires, and literature review to identify user needs and evaluate the system. The educational game was developed using web-based technologies, enabling easy access through a browser without additional installation. The results show that the developed educational game improves children’s learning interest and engagement during the learning process. The system is also considered user-friendly and suitable for early childhood characteristics, both in terms of interface design and interactivity. Therefore, the web-based educational game is feasible and effective as an alternative learning medium to support early childhood education.